Christian Religious Education in the Family: Benefits and Uses for the Millennial Generation - Leonard Lumban Tobing; Lasmaria Nami Simanungkalit (International Journal of Science and Society, 2022)
Christian Religious Education, from now on referred to as family PAK, is a very important education for all family members. Through family PAK, that can be done with worship, with the aim that all family members can know and understand God who is worshiped and enable the whole family to live according to God's word and can be an example for others. Family PAK is an important task for parents as individuals who are given the responsibility by God to teach it. Not only parents but all family members who are there must support each other and carry out PAK in the family; therefore, it takes commitment from the whole family so that family PAK can be realized. Given how many children choose the wrong path (not in the presence of God) to take actions that are not commendable, the child's future will be disrupted. In this case, how do parents give time to teach their children through worship, stories, and conversations. This writing aims to see the extent to which the benefits and objectives of PAK are carried out in the family to anticipate the progress of the era, which greatly influences the human mindset.